Integrated management strategies for fuscous blight and floury leaf spot of rajmash - MONDAL, KALYAN K. (Indian Phytopathology, 2004)
Pseudomonas fluorescens strain RPB14, a dominant member of the rajmash phylloplane, showed potential biocontrol activity against major diseases of rajmash bean (Phaseolus vulgaris) including fuscous blight (Xanthomonas axonopodis pv. phaseoli var fuscans) and floury leaf spot (Ramularia phaseoli) both in vitro and under field conditions. The integrated disease management strategies involving this strain suppressed the diseases significantly and thereby improving the plant health of the rajmash (cv. Baspa). Two foliar applications of the strain RPB14, 1st at seedling (107 cfu ml-1) and 2nd at flowering (106 cfu ml-1), followed by a single spray of carbendazim 50WP (0.05%) at pod developmental stage was best in protecting both the diseases by 59.6 (floury leaf spot) and 51 per cent (fuscous blight) as well as in increasing the seed yield by 81.3 per cent over control. The strain RPB14 could colonize on rajmash both in presence and absence of pathogens. The present study reveals that the strain PRB14 could serve as a potential input in the integrated disease management approaches for rajmash.